Destroy this house : a memoir - Uhle, Amanda (Summit Books, 2025)
"The Long family's love was fierce, their lifestyle bizarre, and their deceptions countless. Once her parents were gone, Amanda Uhle realized she was closer to them than anyone else, yet she found herself utterly confounded by the lives they had led. Amanda's striving fashion designer mother and her charismatic wheeler-dealer father wove a complex life together that spanned ten different homes across five states over forty perplexing years. Throughout her childhood, as her mother's hoarding disorder flourished and her father's schemes crumbled, contradictions abounded. They bartered for dental surgery and drove their massive Lincoln Town Car to the food bank. When financial ruin struck, they abandoned their repossessed mansion for humble parish housing, and Amanda's father became a preacher. They swung between being filthy rich and dirt poor, devious and virtuous, lonely and loved, fake and real. In Destroy This House, Amanda sets out to document her parents' unbelievable exploits and her own hard-won escape into independence. With humor and tenderness, Uhle has crafted a heartfelt and utterly unique memoir, capturing the raucousness, pain, joy, and ultimately, the boundless love that exists between all parents and children." --